Situation Report: Romania, 25 July 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu and Tito Meet in Yugoslavia Ceausescu Discusses Co-operation with Fiat Two Former Interior Ministers Appointed County Party First Secretaries Improving Preschool Education Wheat Harvest Delayed Exchange Rates for Western Currencies Once Again Revised Upward Application of the New Housing Laws